Implementation of Transplantation and Restoration Development Technology as Alternative Income Marine Tourism on Karangrang Island Pangkajene Kepulauan South Sulawesi: Penerapan Teknologi Pengembangan Transplantasi dan Restorasi Sebagai Wisata Bahari Pendapatan Alternatif di Pulau Karanrang Pangkajene Kepulauan Sulawesi Selatan - Paharuddin Paharuddin; Mauli Kasmi; Sulkifli Sulkifli; Irawan Irawan; Andi Ridwan Makkulau; Andryanto Aman (Yayasan Ahmar Cendekia Indonesia, 2022)
Integration technology Ornamental coral transplantation and sustainable restoration for marine tourism is a transformation from the utilization of the results of coral transplantation towards marine tourism. This program is a model of community empowerment for regional development. The aim of the project is to enhance Cobia's creativity through planned and high-quality replanting to ensure sustainability. The method used is to divide the medium and hexagonal corals into finished sized coral slices that are ready to be planted. After constructing and designing the ecological ledges that make up the blind coral, they are built on an artificial platform placed under the sea, making it older than the natural one. Green technology agriculture through community projects for sustainable cultivation and tourism.Improving the quantity and quality of ornamental coral reef resources and marine tourism, developing innovative ideas to present innovative products that can be marketed to industry and society, and accelerating the recovery of marine ecosystems. coral reefs damaged by destructive fishing. AbstrakTeknologi integrasi transplantasi karang hias dan restorasi lestari untuk wisata bahari merupakan transformasi dari pemanfaatan hasil transplantasi karang has kearah wisata bahari. Program ini merupakan salah satu model pemberdayaan masyarakat untuk pengembangan daerah.. Tujuan dari proyek ini adalah untuk meningkatkan kreativitas Cobia melalui penanaman kembali yang terencana dan berkualitas tinggi untuk memastikan keberlanjutan. Metode yang digunakan adalah dengan membagi karang sedang dan heksagonal menjadi irisan karang berukuran jadi yang siap ditanam. Setelah membangun dan merancang tepian ekologis yang membentuk karang buta, mereka dibangun di atas platform buatan yang ditempatkan di bawah laut, membuatnya lebih tua dari yang alami. Pertanian teknologi hijau melalui proyek masyarakat untuk budidaya dan pariwisata yang berkelanjutan. Meningkatkan kuantitas dan kualitas sumber daya terumbu karang hias dan wisata bahari, mengembangkan ide-ide inovatif untuk menghadirkan produk-produk inovatif yang dapat dipasarkan kepada industri dan masyarakat, serta mempercepat pemulihan ekosistem laut. terumbu karang yang rusak akibat penangkapan ikan yang merusak.